2009
DOI: 10.1073/pnas.0812432106
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling bacterial polysaccharides by metabolic pathway engineering

Abstract: Introducing structural modifications into biomolecules represents a powerful approach to dissect their functions and roles in biological processes. Bacterial polysaccharides, despite their rich structural information and essential roles in bacterium-host interactions and bacterial virulence, have largely been unexplored for in vivo structural modifications. In this study, we demonstrate the incorporation of a panel of monosaccharide analogs into bacterial polysaccharides in a highly homogenous manner via metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
115
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 19 publications
0
115
0
Order By: Relevance
“…Recently, Wang et al showed that the His 6 -tagged recombinant FKP from B. fragilis has relaxed specificity toward fucose analogs bearing unnatural substituents at the C-5 position (19). To quantitatively evaluate the specific activity of the recombinant FKP toward C-5 substituted fucose analogs, we determined the fucokinase activity of the recombinant FKP toward a panel of unnatural substrates, using a simple coupled enzymatic assay with a spectophotometric readout.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wang et al showed that the His 6 -tagged recombinant FKP from B. fragilis has relaxed specificity toward fucose analogs bearing unnatural substituents at the C-5 position (19). To quantitatively evaluate the specific activity of the recombinant FKP toward C-5 substituted fucose analogs, we determined the fucokinase activity of the recombinant FKP toward a panel of unnatural substrates, using a simple coupled enzymatic assay with a spectophotometric readout.…”
Section: Resultsmentioning
confidence: 99%
“…Connecting these two domains is a 150-aa linker, whose function is currently unknown. Wang and co-workers demonstrated recently that a His 6 -tagged recombinant FKP, expressed in Escherichia coli, is a promiscuous enzyme with relaxed specificity toward fucose analogs bearing unnatural substituents at the C-5 position (19).…”
mentioning
confidence: 99%
“…Furthermore, this result may also demonstrate the promiscuity of the glycosyltransferases which are responsible for the synthesis of the oligosaccharides that are eventually displayed on the cell surface. In conjunction with the incorporation of modified fucose derivatives into the LPS of E. coli O86:B7, we further demonstrate proof of principle that other unique monosaccharides can be engineered into the cell surface oligosaccharides in bacteria [27]. Unlike our previous work where we could control the exact location of the modification to the LPS, because of the possible pathways that 2-ketoGlc may take, exact identification of which residue is being modified in the core oligosaccharides is challenging.…”
Section: Resultsmentioning
confidence: 94%
“…Previous work by our lab has used E. coli O86 as a model system for the pin point modification of the fucosylated LPS by using metabolic pathway engineering, and in this work we sought to expand our ability to modify this model strain with 2-ketoGlc [27]. Structurally 2-ketoGlc is very similar to GlcNAc, with the exception of the 2 amide, and thus may be incorporated as GlcNAc in the LPS.…”
Section: Labeling Lpsmentioning
confidence: 99%
“…Significantly, exogenous salvage pathways can serve as convenient routes to introduce nonnatural sugar analogs into glycans. For example, an artificial fucose salvage pathway was recently exploited to install fucose analogs into cell-surface polysaccharides of E. coli in which de novo biosynthesis of the donor nucleotide-sugar GDPfucose had been disrupted (31). We conducted several experiments to determine if the GlcNAc salvage pathway in gna1Δ yeast could assimilate unnatural GlcNAc analogs into secreted glycoproteins.…”
Section: Resultsmentioning
confidence: 99%